Improving retrieval of structured and unstructured information: Practical steps for better classification, navigation and search. (June 2017) - Engel, Jonathan
Every day, information users struggle to find relevant documents and data needed to perform their jobs effectively and efficiently. This paper presents a strategic, practical approach to information architecture, focusing on developing and adding metadata to improve information retrieval. The review starts with a discussion of common information management problems and potential business benefits, and addresses the need for overarching principles and policies to be aligned with a comprehensive enterprise architecture. Next, the paper outlines a solution based on combining elements of information architecture – the hierarchy of a taxonomy, the synonyms from a thesaurus and the relationships in an ontology. It discusses how this hybrid structure can improve content classification, user navigation and enterprise search. The final sections will explain how taxonomy-generated rules can improve content classification and search, and present the results of a recent Proof of Concept (PoC) for automated content classification. The article also includes two sidebars – one offering taxonomy best practice guidelines and the other exploring an advanced classification weighting to improve search precision.